2008
DOI: 10.1111/j.1365-3016.2008.00935.x
|View full text |Cite
|
Sign up to set email alerts
|

Placental characteristics and birthweight

Abstract: Standard gross placental measures capture dimensions relevant to specific placental functions. Our objective was to determine their accountability independent of placental weight for variance in birthweight, an important proxy for intrauterine 'adequacy' in fetal origins studies. The sample consisted of 24 152 singleton liveborn children of the Collaborative Perinatal Project delivered from 34 to 42 completed weeks gestation, with complete data for six placental measures (placental disc shape, umbilical cord l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
116
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(128 citation statements)
references
References 31 publications
12
116
0
Order By: Relevance
“…Thus investigations into the impact of the changes in placental vascular architecture are currently underway. Finally, although we did not observe any change in placental weight associated with PAH exposure, these data correspond to those observed in the population of human smokers (44,52,62,69). Thus maternal administration of PAHs in mice can recapitulate the placental vascular changes triggered by smoking in humans.…”
Section: Discussionmentioning
confidence: 47%
“…Thus investigations into the impact of the changes in placental vascular architecture are currently underway. Finally, although we did not observe any change in placental weight associated with PAH exposure, these data correspond to those observed in the population of human smokers (44,52,62,69). Thus maternal administration of PAHs in mice can recapitulate the placental vascular changes triggered by smoking in humans.…”
Section: Discussionmentioning
confidence: 47%
“…Previous reports have suggested that a shift in the centrality of the umbilical cord insertion on the chorionic plate reflects the level of vasculature available for nutrient supply [17,23]. Thus, a greater shift leads to a lower level of vascular distribution available for nutrient exchange (and vice versa) [24].…”
Section: Discussionmentioning
confidence: 99%
“…The developing fetus is obligatorily dependent on the mother for nutrient supply and so maternal adequate nutrition is critical for the provision of the required amounts of nutrients (carbohydrates, proteins and lipids) for the developing fetus [15]. On the other hand, the placenta must be well developed and healthy to ensure that the available nutrients from the mother are delivered to the fetus [16,17]. Comparative studies of maternal socio-demographic factors in various countries and in subSaharan Africa show that young age (and/or maternal age greater than 35), a single motherhood and lifestyle behaviours (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The second pathway affects fetal growth indirectly by modifying the placental nutritional transport and metabolism. Accordingly, the placental weight has been shown to be closely correlated with the birth weight in large studies (40).…”
Section: Discussionmentioning
confidence: 99%